Educational Metaphor in the Polish press: a perspective on presenting the political situation in Poland at the beginning of the Russia–Ukraine war - Adamczuk, Joanna (Vilnius University Open Series, 2024)
The following paper investigates the topic of educational metaphors about the Russia–Ukraine War in Polish press articles. Educational metaphor relates to the use of concepts connected with schooling or teaching in order to describe other concepts. The research material is composed of texts published after 24 February 2022 in the following newspapers: Do Rzeczy, Gazeta Polska, Polityka, and Krytyka Polityczna. This article aims to present one of the metaphorical mappings together with its critical analysis with the use of the conceptual metaphor theory (Лакофф, Джонсон 2004) and critical metaphor analysis (Charteris-Black 2004). According to the research, the trichotomy which includes the Polish Government, the opposition parties, and the Polish society may be distinguished in the Polish press. Amidst these oppositions, the metaphorical mapping is discerned, according to which the war is understood as the teacher, the politicians and society as the students, and the help offered to Ukraine is interpreted as the examination. Assessment of the actions undertaken by the Government, the opposition parties and the society has been the subject of the ideological and political profile of a particular magazine.
Keywords: Russia–Ukraine war; conceptualisation; metaphor; Polish press